Evaluations for Community Vocational Training Centers to Become Business Incubators in East Java, West Nusa Tenggara, and East Nusa Tenggara - Hisyam Fahmi; Ahmad Abtokhi; Ridwan; Musataklima; Abdul Aziz; Shalih Husni; Noor Rizqiya Fimaulidina; Puji Lestari; Hamdani (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: This study addresses the broader issue of enhancing the economic impact and sustainability of community vocational training centers (BLKK). It focuses on the BLKK programs in East Java, West Nusa Tenggara, and East Nusa Tenggara, with the purpose of evaluating their potential to evolve beyond training facilities into effective business incubators that foster community entrepreneurship. Purpose of the Study: The purpose is to assess the capacity of BLKK centers to function as business incubators. The objectives are to identify the critical factors—such as human resources, leadership, environment, and collaboration—necessary for this transition and to provide actionable recommendations for improvement. Methods: The study employs a mixed-methods approach, utilizing field visits and questionnaires to collect empirical data from the targeted BLKK centers. The analysis is framed within a holistic perspective that considers integrated organizational and ecosystem development. Results: The findings underscore that transforming BLKK centers into effective incubators requires a comprehensive strategy. Key recommendations include aligning training curricula with market demands, improving tenants' access to capital, expanding professional and business networks, and instituting robust post-incubation support mechanisms. The study concludes that continuous monitoring and evaluation, coupled with these strategic enhancements, are vital for developing a competent workforce and promoting sustainable business practices within the community.